1965
DOI: 10.1901/jeab.1965.8-263
|View full text |Cite
|
Sign up to set email alerts
|

SOLUTION OF THE INTERMEDIATE SIZE PROBLEM BY PIGEONS1

Abstract: Pigeons learned to respond to the middle-sized member (SD) of a set of three simultaneously presented stimuli with responses to the SD reinforced on a VI 1 schedule. They were then tested for several days with other sets of three stimuli. One procedure presented reinforcements on a VI 1 schedule during the test independent of the stimulus chosen when a reinforcement was programmed. The tests were also given under extinction conditions. With the testing carried out with extinction, preference consistently was f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
3
0

Year Published

1967
1967
2022
2022

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(4 citation statements)
references
References 11 publications
1
3
0
Order By: Relevance
“…With the 1.4:1 probes, Birds 4 and 6 preferred different stimuli but both responded most to the same one of the two stimuli in each of the two sets. These findings completely replicated earlier results (Zeiler, 1965;Zeiler and Price, 1965) in showing that the similarity of stimuli to S+ controlled the responses.…”
Section: Responses In the Probessupporting
confidence: 89%
See 2 more Smart Citations
“…With the 1.4:1 probes, Birds 4 and 6 preferred different stimuli but both responded most to the same one of the two stimuli in each of the two sets. These findings completely replicated earlier results (Zeiler, 1965;Zeiler and Price, 1965) in showing that the similarity of stimuli to S+ controlled the responses.…”
Section: Responses In the Probessupporting
confidence: 89%
“…Recent research also studied preferences with each test set but supplemented this information with quantitative data to indicate the degree of functional equivalence between the training and the test stimuli (Honig, 1962;Zeiler, 1965;Zeiler and Price, 1965). The experimental procedure enabling the acquisition of this additional information was a variation of the Guttman and Kalish (1956) technique for studying stimulus generalization.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Any reinforcement during testing causes problems to some degree. A number of studies (e.g., Zeiler, 1965) have demonstrated that reinforcing responses to novel stimuli on tests with a primary reinforcer tends to bias -further testing. Extinguishing responses on tests also can create problems.…”
Section: Methodsmentioning
confidence: 99%